Observing the EFL Students’ 21st Century Skill Performance through Learning Activities of Research on the ELT Course - Hadiyanto Hadiyanto (Universitas Jambi, Indonesia, 2021)
Students’ 21st-century skills; soft skills, and hard skills were developed through student-centered e-learning (SCEL) activities in Research on the ELT Course. The current study was conducted to improve teachers’ instructional strategies in e-learning to enhance students’ 21st-century skills through their learning activities. Data were gained by observing and assessing 24 students’ performance in practicing 21st-century skills through SCEL activities. Teachers have successfully improved instruction techniques and encourage students to learn in a group, independently, using online resources, discussion, and video presentations, as the result, the students’ 21st-century skills could be improved from cycle to cycle. Each SCEL activity developed certain soft skills and hard skills components differently. In conclusion, the teacher successfully applied SCEL activities to engage and enhance students’ 21st-century skills. The findings implicated that teachers should be more creative and innovative in using e-learning for teaching and learning to create an active online learning environment and enhance students’ 21ts century skills. Further research is expected to apply an experimental research design to search for the most effective method and measure the level of effectiveness of e-learning usage for the students’ 21st-century skills development.